Dar dėl ide. fleksinės sistemos atsiradimo - Palmaitis, Letas (Baltistica, 1975)
MORE ON THE ORIGIN OF INDO-EUROPEAN INFLECTED SYSTEM As investigations in the field of Afro-Asiatic languages show, the primary Afr.-A. vocalism may be represented as an opposition а – ə, -a and -ø being allophons in ultima. Therefore the fact that according to V. Ivanoff – E. Pulleyblank the primary I.-E. opposition may be reinterpreted as а – ə, enables us to suppose it’s universality in all West-Borealic dialects. So the I.-E. vocalism in ultima may be also identified as -a‖-ø – ə – cf. e. g. Hittite datives-locatives with zero inflection and with -a. It seems possible, that in C-stems’ endings the zero variant was generalized, while in a-stems it was the a-variant. In this way the thematic suffix -a may have arised. The gender system which preceded the I.-E. trigender system was like that of Afr.-A. type, part of the former common gender having been turned into “masculinum”, the other part as well as the former neutral (non neutrum!) gender having formed an “intermediate” gender (genus Σ). I.-E. sg. fem. = pl. neutr. were mostly nomina abstracta derivated from the “intermediate” gender stems by adding H2 (а/ə stem ending + H2 = ā, or ø stem ending +H2) (see table). It is possible that Proto-I.-E. derivations with ā having been descended from the primary *a/ət2 > *а/əНг, like Afr.-A. -ā < -ah < -at, t being a common Borealic formative pointing to passivity and abstraction.